Jump load and landing patterns of collegiate female volleyball players during practice and competition - Taylor, J. B.; Kantor, J. L.; Hockenjos, T. J.; Barnes, H. C.; Dischiavi, S. L. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Overuse lower extremity injuries are common in women`s court volleyball players and are likely due to the repetitive jumping and landing the sport requires. The purpose of this study was to quantify jump load during collegiate women`s volleyball, describe the quantity of double-leg (DL) to single-leg (SL) landing strategies, and compare loads and landing strategies between games and practices. METHODS: Fourteen collegiate Division-1 women`s court volleyball players participated in the study. Volleyball-specific activity demands were quantified using video analysis from three consecutive practices and one match. Investigators recorded the total frequency of jump landings, and the frequency and percentage of double-leg (DL) landings and single-leg (SL) landings of fourteen collegiate Division-1 women`s court volleyball players. Repeated measures ANOVAs identified differences in jumping load and percentages of DL and SL landings among practices and between practices and games (P<0.05). RESULTS: On average, there was a significantly higher overall jumping load (P=0.01) and frequency of DL (P=0.03) and SL (P=0.04) landings during practice than games, yet no differences between practices (P>0.05). Approximately 75% of all landings were DL, and individual patterns of DL to SL landings were consistent across events (P>0.05). CONCLUSIONS: Women`s collegiate volleyball demands high volumes of repetitive jumping and landing with SL and DL support that may make these athletes susceptible to overuse injuries, especially during practice.